Numerical Study of Hydrogen Enrichment on Stoichiometric DME–Air Premixed Flames - Aris Purwanto; Herman Saputro; Akhmad Faruq Alhikami; Riyadi Muslim; Eka Dwi Ariyanto; Fudhail Abdul Munir (Automotive Experiences, 2026)
Dimethyl ether (DME), an alternative fuel lacking carbon–carbon bonds, offers the potential for clean combustion with minimal soot emissions. Despite this advantage, DME exhibits relatively low initial reactivity and flame-propagation velocity under premixed conditions, which constrains its stability and operational flexibility. This study presents a numerical investigation of hydrogen enrichment effects on DME–air combustion characteristics and mechanisms, with emphasis on microkinetic behavior and flame structure. The investigation employs one-dimensional (1D) and two-dimensional (2D) simulations to assess adiabatic flame temperature, laminar flame propagation velocity, elementary reaction rates, dominant reaction pathways, and distributions of temperature and OH radicals. Results from 1D simulations indicate that introducing hydrogen at low fractions (approximately 5%) markedly increases both flame temperature and propagation velocity by enhancing the H–O–OH radical pool. When hydrogen fractions exceed 10%, further improvements in combustion performance plateau as the system nears chemical equilibrium. Kinetic analysis reveals that hydrogen acts as a key modulator, shifting DME oxidation from initiation-dominated reactions to hydrogen-abstraction and chain-branching regimes. Two-dimensional simulations corroborate that this mechanistic shift produces a more compact flame, advances heat release, and increases the concentration of OH radicals by an order of magnitude. Collectively, these results demonstrate that hydrogen functions as a microkinetic enhancer rather than merely a fuel additive and indicate that moderate enrichment (5–10%) is sufficient to optimize DME combustion.